2021
DOI: 10.1038/s41598-021-83102-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning identifies morphological features in breast cancer predictive of cancer ERBB2 status and trastuzumab treatment efficacy

Abstract: The treatment of patients with ERBB2 (HER2)-positive breast cancer with anti-ERBB2 therapy is based on the detection of ERBB2 gene amplification or protein overexpression. Machine learning (ML) algorithms can predict the amplification of ERBB2 based on tumor morphological features, but it is not known whether ML-derived features can predict survival and efficacy of anti-ERBB2 treatment. In this study, we trained a deep learning model with digital images of hematoxylin–eosin (H&E)-stained formalin-fixed pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…ERBB2 amplificationeassociated morphology extracted from H&E images of breast cancer also correlated with the efficacy of adjuvant trastuzumab therapy and had a favorable effect on distant disease-free survival in CISH ERBB2-positive patients. 44 Another deep-learning model exceeded the performance of experienced gastrointestinal pathologists predicting microsatellite instability from H&Estained WSIs. 45 More importantly, these methods also allowed localization of the tumor areas responsible for this classification, which help in highlighting biologically and clinically relevant ITH aspects of the tumor morphology.…”
Section: Implicit Feature-based Modelsmentioning
confidence: 99%
“…ERBB2 amplificationeassociated morphology extracted from H&E images of breast cancer also correlated with the efficacy of adjuvant trastuzumab therapy and had a favorable effect on distant disease-free survival in CISH ERBB2-positive patients. 44 Another deep-learning model exceeded the performance of experienced gastrointestinal pathologists predicting microsatellite instability from H&Estained WSIs. 45 More importantly, these methods also allowed localization of the tumor areas responsible for this classification, which help in highlighting biologically and clinically relevant ITH aspects of the tumor morphology.…”
Section: Implicit Feature-based Modelsmentioning
confidence: 99%
“…Recent studies have shown that a wide range of molecular features, including MSI/dMMR status and BRAF mutational status, can be predicted from digitized slides of CRC using deep learning, an artificial intelligence technology [9][10][11][12][13][14]. The application of such methods is not limited to CRC but has been demonstrated in bladder cancer [15], breast cancer [16,17], sarcoma [18], head and neck cancer [19], hepatocellular carcinoma [20], and several other types of solid tumor [8,12]. Therefore, in the future, deep learning could supplement current molecular testing strategies in solid tumors and could be used as a tool for translational research [21].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we hope that in the future biomedical DL research will go beyond representation learning and will be used to derive novel biological knowledge by e.g. inferring synthetic and retrosynthetic chemical reactions, identifying novel diseaseassociated druggable proteins and clinically actionable biomarkers [129][130][131].…”
Section: Discussionmentioning
confidence: 99%